Penerapan Model POE Dalam Meningkatkan Motivasi dan Hasil Belajar IPA - Suryana Suryana (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This research was conducted in class III SD Negeri 050756 Alur Dua Year Learning 2016/2017 with the number of students 20 people 9 male students and 11 female students. The results showed that there was an increase in motivation and student learning outcomes after the learning action through the application of the POE learning model. Achievement of student learning outcomes, the average grade continues to increase from 58.00 at the initial conditions to 66.00 in the first cycle, and in the second cycle to 76.00 with a level of mastery learning 2 students (10%) in the initial conditions , to 11 students (55%), and in the last cycle to 19 students (95%). The motivation to learn from 4 students (20%) in the initial condition became, 12 students (60%), and at the end of the second cycle became 100% motivated learning on the implementation of learning process. The conclusion of the research result shows that POE Learning Model proved to be able to increase the motivation and result of student learning of class III SD Negeri 050756 Alur Dua sub districts Sei Lepan Langkat Regency year 2016/2017. Keyword: predict, observe, explain Abstrak: Penelitian ini dilakukan di kelas III SD Negeri 050756 Alur Dua Tahun Pelajaran 2016/2017 dengan jumlah siswa 20 orang 9 orang siswa laki-laki dan 11 orang siswa perempuan. Hasil penelitian menunjukkan adanya peningkatan motivasi dan hasil belajar siswa setelah tindakan pembelajaran melalui penerapan model pembelajaran POE. Pencapaian hasil belajar siswa, nilai rata-rata kelas terus mengalami peningkatan dari 58,00 pada kondisi awal menjadi 66,00 pada siklus pertama, dan pada siklus kedua menjadi 76,00 dengan tingkat ketuntasan belajar 2 orang siswa (10%) pada kondisi awal, menjadi 11 siswa (55%), dan pada siklus terakhir menjadi 19 siswa (95%). Motivasi belajar dari 4 siswa (20%) pada kondisi awal menjadi, 12 siswa (60%), dan pada akhir siklus kedua menjadi 100% termotivasi belajarnya pada pelaksanaan proses pembelajaran. Kesimpulan hasil penelitian menunjukkan bahwa Model Pembelajaran POE terbukti dapat meningkatkan motivasi dan hasil belajar siswa kelas III SD Negeri 050756 Alur Dua kecamatan Sei lepan Kabupaten Langkat tahun pelajaran 2016/2017. Kata kunci: predict, observe, explain